2017
DOI: 10.1007/s12630-017-0971-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of the effectiveness of nasal intubation using a GlideScope video laryngoscope with Magill forceps versus vascular forceps in patients with a normal airway

Abstract: PurposeThe GlideScope® video laryngoscope (GVL) is widely used for nasotracheal intubation in dental and facial plastic surgery. The angle of the Magill forceps is different from that of the GVL blade, which suggests that the Magill forceps are not the ideal forceps for use with the GVL. The purpose of this study was to compare the effectiveness of the Magill forceps vs vascular forceps for nasotracheal intubation using the GVL.MethodsThis study included 60 patients scheduled to undergo elective surgery requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The total NTI time, which was de ned as the period from when the operator picked up the device to when three successive end-tidal carbon dioxide waves were obtained following intubation [12], was recorded. An observer blinded to the group assignments assessed epistaxis bleeding using direct laryngoscopy after five minutes of completing NTI, and it was scored as one of four grades according to the following modified criteria: no epistaxis (no blood observed on either the surface of the tube or the posterior pharyngeal wall); mild epistaxis (blood apparent on the surface of the tube or posterior pharyngeal wall); moderate epistaxis (pooling of blood on the posterior pharyngeal wall); and severe epistaxis (a large amount of blood in the pharynx that impeded NTI and necessitated urgent orotracheal intubation) [13].…”
Section: Methodsmentioning
confidence: 99%
“…The total NTI time, which was de ned as the period from when the operator picked up the device to when three successive end-tidal carbon dioxide waves were obtained following intubation [12], was recorded. An observer blinded to the group assignments assessed epistaxis bleeding using direct laryngoscopy after five minutes of completing NTI, and it was scored as one of four grades according to the following modified criteria: no epistaxis (no blood observed on either the surface of the tube or the posterior pharyngeal wall); mild epistaxis (blood apparent on the surface of the tube or posterior pharyngeal wall); moderate epistaxis (pooling of blood on the posterior pharyngeal wall); and severe epistaxis (a large amount of blood in the pharynx that impeded NTI and necessitated urgent orotracheal intubation) [13].…”
Section: Methodsmentioning
confidence: 99%
“…We appreciate the keen interest and thoughtful comments by Dr. Turkstra 1 on our study 2 where we found that using a forceps-guided tube exchanger could be advantageous when using the GlideScopeÒ videolaryngoscope (GVL; Verathon Medical Inc., Bothell, WA, USA) for oral endotracheal tube (ETT) intubation. The reason for an advantage might be the flexibility and pliability of a tube exchanger.…”
Section: To the Editormentioning
confidence: 98%
“…2 Before study implementation, three operators were trained in nasal intubation using a GVL. As mentioned above, the two different forceps were used in both groups.…”
Section: To the Editormentioning
confidence: 99%
“…To the Editor, I read with interest and would like to comment on the recent randomized clinical trial reported by Yeom et al 1 regarding nasal intubation using a GlideScope videolaryngoscope (GVL; Verathon Medical Inc., Bothell, WA, USA). In that study, 1 the authors examined the time for nasal GVL intubation using vascular forceps and an airway exchange catheter compared with the standard Magill forceps originally described for direct laryngoscopy.…”
mentioning
confidence: 99%
“…2,3 This seems intuitive as the Magill forceps was not designed for use with videolaryngoscopy and does not have suitable geometry for this task. [1][2][3] In addition, it is unfortunate that Yeom et al 1 do not specify the frequency of forceps use in either group of their study, particularly as forceps use (or lack thereof) is part of the intervention being studied. It would be helpful to know if forceps were used in either group.…”
mentioning
confidence: 99%